Preparation of fresh gluten free pasta enriched with açaí waste flour (Euterpe oleracea Mart.) and bacaba (Oenocarpus bacaba mart.) (Research, Society and Development, 2021)
The present study aimed to develop and characterize fresh pasta type noodles, with partial replacement of rice flour by the flour of the açaí seed FCA and of the FCB bacaba shell, and to evaluate its physical-chemical characteristics, proximal composition, color, technological properties and texture profile. For this purpose, five mass formulations were prepared, replacing control mass (MC), containing 5% (FCA), 10% (FCA), 5% (FCB) and 10% (FCB). The humidity of the pasta presented a maximum percentage of 35%, so they are in accordance with the Brazilian legislation in force for fresh pasta. Pasta formulations with FCA showed higher levels for protein and ash at 10%. For FCB formulations it showed a higher content of lipids. Regarding energy values, pasta enriched with FCA and FCB can be seen as a food rich in calories, according to Brazilian legislation. As for technological properties, the addition of flours to the doughs caused a statistical difference in the parameter of the increase in dough. The color analysis, the chroma parameters (C *) and the hue angle (H *) obtained results that interfered with the color, indicating the pure red tint for both FCA and FCB pasta. Regarding the parameters of texture, hardness, guminess and chewability, all concentrations of FCA and FCB showed a significant difference when compared to MC. Pasta made with different concentrations of FCA and FCB has provided variations in ingredients, in addition to contributing to the environment, since waste disposal will be reduced.